Perbandingan Simulasi Pengukuran Aliran Gas Menggunakan USM Dengan Simulasi Melalui Aplikasi Kelton Pada Proyek Pipa Gas di PT. X (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
Comparing gas flow measurement results using Ultrasonic Sensor Meters and Kelton software is very important because the objective is to determine whether the errors that occur are in accordance with applicable standards or not. This study aims to compare the simulation results from the Ultrasonic Flow Meter (USM) with Kelton software based on AGA 8, AGA 9, and ISO 6976 regulations. From measurements with the USM, an error value of 0.01% was obtained, while from Kelton software, an error value of 0.01% was also obtained. Thus, it can be concluded that the readings from both methods are still within the specified error tolerance range of 0.1%, so they do not cause excessive cost losses during the gas delivery process. This proves that the Ultrasonic Sensor Meter used has the ability to measure accurately, making it suitable for use as a measuring device in gas metering systems.